Hedonic test and chemical organoleptic and chemical characteristics of cork and toman fish emping - Kartikasari, Dewi; Khairina, Rita; Wahyono, M. Dwiki (Journal of Agritechnology and Food Processing, 2023)
Local fish species from the waters of South Kalimantan that are a source of protein and high in albumin are cork fish and toman fish. In an effort to increase the value added and consumption of both fish, it is necessary to diversify the product, for example by processing them into fish emping. Emping is a type of round and thin snack generally made from melinjo seeds, which are flaked, dried and then fried.  The aim of this study was to determine the organoleptic and chemical characteristics of cork and toman fish emping. This study consisted of 2 treatments, namely the cork fish puff and the toman fish puff. To determine the difference between the two treatments, data analysis was carried out using independent t-test with test parameters including yield calculation, hedonic test (taste, colour, aroma and texture) and chemical test (water, ash, protein, fat, carbohydrate, fibre, energy, TKE and TKP). Based on the results of the t-test, it is known that the organoleptic characteristics of the two empings show a significant difference, with the cork emping being more favourable than the toman emping. The chemical characteristics did not show any significant difference. In conclusion, the yield characteristics, moisture content, ash, protein, fat, carbohydrate, fibre, energy, energy sufficiency level (TKE) and protein sufficiency level (TKP) of cork fish cake were 4.07%, 66.66%, 2.67%, 7.22%, 0.95%, 319.52 kcal, 20.97% and 202.00% respectively with a yield of 10.10%. For toman, the values were 19.29%, 4.31%, 66.89%, 2.55%, 6.96%, 1.02%, 318.37 kcal, 20.54% and 202.69% with a yield of 10.83%. Thus, both cork and toman fish cake are high protein products.